Avaliação das práticas de ecodesign em empresa do setor da moda: o caso da empresa 2Primas - Rufino, Débora Aparecida Alves (2014)
This study seeks to understand the use of ecodesign practices in the clothing firm 2PRIMAS, using the conceptual model of Rozenfeld et al. (2006) as analysis. The segment of this fashion company is an activity of great economic importance according to ABIT (Brazilian Association of Textile and Garment). Only in January 2013 the sector generated 7,152 jobs from 2,148 in the same period of 2012. The methodology of this study is of qualitative and exploratory nature. Therefore, a case study was used. The object of study was a company that operates in the fashion industry and it is in the market as a sustainable brand, which its aims are the production and development of products for the acceptance of ecodesign practices. The following concepts were used: (1) sustaintability and the fashion – they are described as sustainability initiatives which are the latest in the fashion industry; (2) concepts of ecodesign – besides the concepts of this practice, the requirements are given for the implementation of it in the organization; (3) business strategies – it brings a discourse related to the strategy concepts and their importance in the business environment, and how it can be relevant to sustainability initiatives in an organization; and (4) the fashion industry – It was needed a study of this sector; therefore, the importance of their activities to the Brazilian economy and the impacts their products cause to the environment. At the end of this case study it was evaluated the practices of ecodesign in the company here studied and it has been made some suggestions for its processes improvement.